Antibacterial Peptide BSN-37 Kills Extra- and Intra-Cellular Salmonella enterica Serovar Typhimurium by a Nonlytic Mode of Action - Yang, Lei; Sun, Yawei; Xu, Yanzhao; Hang, Bolin; Wang, Lei; Zhen, Ke; Hu, Bing; Chen, Yanan; Xia, Xiaojing; Hu, Jianhe (Frontiers in Microbiology, 2020)
The increasing rates of resistance to traditional anti-Salmonella agents have made the treatment of invasive salmonellosis more problematic, which necessitates the search for new antimicrobial compounds. In this study, the action mode of BSN-37, a novel antibacterial peptide (AMP) from bovine spleen neutrophils, was investigated against Salmonella enterica serovar Typhimurium (S. Typhimurium). Minimum inhibitory concentrations (MICs) and time-kill kinetics of BSN-37 were determined. The cell membrane changes of S. Typhimurium CVCC541 (ST) treated with BSN-37 were investigated by testing the fluorescence intensity of membrane probes and the release of cytoplasmic β-galactosidase activity. Likewise, cell morphological and ultrastructural changes were also observed using scanning and transmission electron microscopes. Furthermore, the cytotoxicity of BSN-37 was detected by a CCK-8 kit and real-time cell assay. The proliferation inhibition of BSN-37 against intracellular S. Typhimurium was performed in Madin-Darby canine kidney (MDCK) cells. The results demonstrated that BSN-37 exhibited strong antibacterial activity against ST (MICs, 16.67 µg/ml), which was not remarkably affected by the serum salts at a physiological concentration. However, the presence of CaCl2 led to an increase in MIC of BSN-37 by about 4-fold compared to that of ST. BSN-37 at the concentration of 100 µg/ml could completely kill ST after co-incubation for 6 h. Likewise, BSN-37 at different concentrations (50, 100, and 200 µg/ml) could increase the outer membrane permeability of ST but not impair its inner membrane integrity. Moreover, no broken and ruptured cells were found in the figures of scanning and transmission electron microscopes. These results demonstrate that BSN-37 exerts its antibacterial activity against S. Typhimurium by a nonlytic mode of action. Importantly, BSN-37 had no toxicity to the tested eukaryotic cells, even at a concentration of 800 μg/ml. BSN-37 could significantly inhibit the proliferation of intracellular S. Typhimurium.